Analisis Lini Produksi Di Pt. XYZ Menggunakan Simulasi Untuk Meningkatkan Pendapatan - widodo, rizki ari; Yusnawati; Nadya, Yusri; Dewiyana; Novianda; Nurmalawati; Handayani , Nurlaila (E-Jurnal Universitas Samudra, 2026)
PT. XYZ is one of the black tea producers in Indonesia that faces bottleneck problems at the drying station, which hinders the smoothness of the production process. This study aims to identify the standard time at each machine and optimize the production process using simulation with the ProModel software. The research method employed is a quantitative approach with primary data collected through direct observation using a stopwatch and secondary data obtained from the company and literature studies. The simulation results indicate bottlenecks occurring at the Two Stage Drier and Packer machines. Improvement proposals include repairing the Two Stage Drier and adding an additional Packer machine. After implementing the improvements, the utility value of the Two Stage Drier decreased from 12.56% to 6.28%, and the Packer machine from 10.22% to 5.11%. This reduction indicates a significant improvement in efficiency and a decrease in bottlenecks. The feasibility analysis shows that the proposed improvements are viable, with a Net Present Value (NPV) of Rp5.654.165.129.951, a payback period of 0.0123 years (approximately 4 day), and a profit in the first year of Rp497.775.900.960. Therefore, production simulation using ProModel has proven effective in improving the company’s production process efficiency. Keywords: Bottleneck, ProModel Simulation, Standard Time, Production Optimization, Feasibility Analysis.